2016
DOI: 10.1002/ar.23383
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CD14 (Cluster of Differentiation 14) and Toll‐Like Receptor (TLR) 4 Signaling Deteriorate Periapical Inflammation in TLR2 Deficient Mice

Abstract: Apical periodontitis (periapical lesions) is an infection-induced chronic inflammation in the jaw, ultimately resulting in the destruction of apical periodontal tissue. Toll-like receptors (TLRs) are prominent in the initial recognition of pathogens. Our previous study showed that TLR4 signaling is proinflammatory in periapical lesions induced by a polymicrobial endodontic infection. In contrast, the functional role of TLR2 in regulation of periapical tissue destruction is still not fully understood. Using TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…On the other hand, the TLR4 signaling depends on other co-receptors such as CD14, LBP, and MD2 2 , 10 , 22 . According to Rider, et al 24 (2016), TLR2 signaling is an endogenous suppressor of cellular CD14 expression. This mechanism prevents overactive CD14/TLR4-mediated inflammation against microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the TLR4 signaling depends on other co-receptors such as CD14, LBP, and MD2 2 , 10 , 22 . According to Rider, et al 24 (2016), TLR2 signaling is an endogenous suppressor of cellular CD14 expression. This mechanism prevents overactive CD14/TLR4-mediated inflammation against microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…The study was reviewed and approved by the institutional ethics committee of Tokyo Medical and Dental University (approval D2014-039). Animals SAA1.1/2.1 double knockout (dKO; de Beer et al 2010), SAA3 knockout (KO), TLR2 KO, TLR4 KO (Hoshino et al 1999), and TLR2/4 dKO (Rider et al 2016) mice were employed in this study. Frozen sperm of the SAA3 KO strain and breeding pairs of TLR2 KO mice (B6.129-Tlr2 tm1Kir /J) were purchased from the Knockout Mouse Project at the University of California-Davis and The Jackson Laboratory, respectively.…”
Section: Human Periapical Surgical Specimensmentioning
confidence: 99%
“…TLRs recognize pathogen-associated molecular patterns (PAMPs), such as bacterial or viral components, and endogenous mediators, such as proteins and proinflammatory cytokines (3). Previous studies in experimental animals (4)(5)(6) and in humans (7) have demonstrated that TLRs play an important role in the AP pathogenesis.…”
Section: Introductionmentioning
confidence: 99%